Analisis Kuantitas, Kualitas, dan Kontinuitas Air di Sejumlah Pelanggan PDAM Tangkiling - Laurensia, Cindy; Saputra, Raden Haryo; Jaya, Allan Restu (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
This study aims to find out how the level of demand for clean water from the PDAM that is used by some people in the Bukit Batu District area in terms of technical factors and economic factors. Because there are several problems for PDAM Tangkiling related to public complaints about the pungent smell of chlorine, cloudy water, and bad taste that affect the number of customers, a study was conducted on the quantity of water used in each household, the quality of clean water from the PDAM that is used by some people in the Bukit Batu District as a fulfillment of their daily needs, and the continuity of the flow in PDAM Tangkiling and the level of customer satisfaction with PDAM Tangkiling services. This study uses the literature study method from data owned by PDAM Tangkiling. The analysis results show the quantity of water in PDAM Tangkiling regarding technical factors; as much as 63% of respondents stated that the distributed water meets the need for clean water. The quality of the water was distributed to several customers of PDAM Tangkiling; as many as 80% of respondents said that the water quality was cloudy, as many as 67% of respondents said that the quality of the water smelled, and as many as 56%respondents said water tasted .The continuity of water flow to several PDAM Tangkiling customers is scheduled daily for 12 hours, from 05 a.m to 05 p.m. Based on the research results, the linear regression equation is obtained as follows: Y = 0.285X1 + 0.396X2 + 0.386X3, and the mileage of each variable is positive.